Evolusi Diagnostik Sifilis Menggunakan PCR: Komparasi Metode Pemeriksaan di Indonesia dan Luar Negeri Dalam Rentang Tahun 2015-2026 - Jesslyn Widya Salim; Sara A. J. Simanullang; Kasamira S. U. Sau; Joy Miracle Tumigolung Kawer; Maroloan Aruan (JOURNAL SAINS STUDENT RESEARCH, 2026)
Syphilis is a sexually transmitted disease that still has a high number of cases so it is still included in the global problem, this disease is caused by Treponema pallidum, in detecting syphilis the method that is widely used is the serological test as the main test in its detection, but because syphilis can spread quickly and easily undetected, a more accurate and sensitive method is needed. The method is a molecular method, namely Polymerase Chain Reaction (PCR), this method has high sensitivity and specificity so it can be used to detect syphilis. Indonesia is one of the countries that has a high rate of syphilis cases so the PCR method is needed to help in syphilis detection, but it should be noted that PCR is not cheap and easy so its spread and development in Indonesia must be considered by comparing it with existing data abroad or internationally. The method used is a systematic literature review (SLR) which is by collecting original research articles from various journal sources such as PubMed, Google Scholar, ScienceDirect, and other journal sources that have the keywords "Syphilis", "Treponema pallidum", and "PCR" and in the range of 2015 to 2026. The results obtained are 21 articles from abroad or internationally which show that the use of PCR in syphilis detection has been used in 2015, while Indonesia still uses many serological methods such as rapid and started using PCR in 2020 and above such as conventional PCR, multiplex PCR, and also nested PCR. Through the data obtained, it can be seen that the development and distribution of PCR methods for detecting syphilis in Indonesia is still not as sophisticated as abroad or internationally but has begun to increase and develop for the coming years.